Phenomenology of the Dominant Environment in Public Sector Accounting Education from the Perspective of Graduates in Public Sector Accounting - Sajad Naghdi; Roghayye Jeddi (بررسی‌های حسابداری و حسابرسی)
Objective One of the multifaceted studies that has received less attention in the accounting literature is the topic of public-sector accounting education. In contrast, this topic significantly impacts the advancement of public sector goals. For this reason, and due to the necessity of creating an appropriate position for public sector accounting in Iran, a public sector accounting minor was added to the graduate level of accounting for the first time since 2017. The curriculum for this field was authorized by the Development and Planning Council of the Ministry of Science in 2018. However, despite the many successes in establishing this field, due to the low capacity for accepting students and its centralization in the two cities of Karaj and Tehran, universities have not been very successful in educating and training the human resources needed by the public sector. Therefore, the purpose of the current research is to analyze the attitudes and lived experiences of public-sector accounting graduates regarding public-sector accounting education in Iranian universities. Methods In this research, a phenomenological approach was used to understand the lived experiences of accounting graduates in the public sector. The statistical population of the research includes all accounting graduates majoring in public sector accounting, who were selected using the purposeful sampling method. Fifty-three individuals were selected to reach theoretical saturation, and the main method of data collection was an unstructured interview with open-ended questions. This provided the participants with the opportunity to fully describe their experiences regarding public sector accounting education. In the current research, data analysis was conducted in five steps, using Giorgi's method.